Dora Gabe i Anna Kamieńska — dialogi poetyckie - Kovacheva, Adriana (Przekłady Literatur Słowiańskich, 2012)
Dora Gabe i Anna Kamienska — poetic dialogues In this article poetic dialogues between the women poets and translators are represented as a conversation about the mother who is an inspiration for their artistic creativity. From this point of view the translation practice of Dora Gabe is described as palimpsest, because it gives the opportunity for the language to expand so there is place for another, foreign language in its boundaries. In the process of erasing of the Polish source-text, the Bulgarian target-text is being fulfilled with translators’ creative energies. This translation strategy disrupts the stereotypical reception model of Polish poetry in Bulgaria, popularized by Boian Penev. It overcomes its asymmetrical patterns. Svetla Gurova’s and Blaga Dimitrova’s translations are analyzed as continuation of the palimpsest translation model, introduces by Dora Gabe. Key words: Bulgarian poetry, translation strategies, models of literary reception, women translators, gender and translation.